2013
DOI: 10.1002/ece3.388
|View full text |Cite|
|
Sign up to set email alerts
|

Degraded Environments Alter Prey Risk Assessment

Abstract: Elevated water temperatures, a decrease in ocean pH, and an increasing prevalence of severe storms have lead to bleaching and death of the hard corals that underpin coral reef ecosystems. As coral cover declines, fish diversity and abundance declines. How degradation of coral reefs affects behavior of reef inhabitants is unknown. Here, we demonstrate that risk assessment behaviors of prey are severely affected by coral degradation. Juvenile damselfish were exposed to visual and olfactory indicators of predatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 45 publications
0
54
2
Order By: Relevance
“…However, chemosensory cues can be limited by water currents, chemicals released by other organisms (e.g. bleaching corals [49]) and the associated impacts of climate change (e.g. ability of individuals to respond to chemical alarm cues [5,19]).…”
Section: Discussionmentioning
confidence: 99%
“…However, chemosensory cues can be limited by water currents, chemicals released by other organisms (e.g. bleaching corals [49]) and the associated impacts of climate change (e.g. ability of individuals to respond to chemical alarm cues [5,19]).…”
Section: Discussionmentioning
confidence: 99%
“…Fish captured in light traps had no previous association with the fish community associated with the hard reef and were naive to bottom-dwelling predators that feed on juvenile and adult life stages [18]. Previous research on P. amboinensis has found that the newly settled fish have an innate antipredatory response to damage-released chemical cues from the skin of conspecifics both in the field and laboratory [27]. This antipredatory response involves reduced foraging and activity, and increased shelter use, and is similar to the reaction shown in many other damselfishes (e.g.…”
Section: Materials and Methods (A) Study Species And Locationmentioning
confidence: 99%
“…chemical alarm cues), (ii) predator odour and (iii) seawater (blank control). The behaviour of focal fish was quantified for 3 min before (pre-stimulus period) and 3 min after (post-stimulus period) the addition of a test cue (as per previously established protocols [9,27]. Cues were delivered to the focal fish through a delivery tube positioned upcurrent of the patch reef as previously described (60 ml cues þ 60 ml seawater flush).…”
Section: (B) Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, responses of fish to damage-released odours has predominantly focussed on prey species such as damselfish (Pomacentridae) [17, 23]. In healthy coral habitats, damselfishes respond innately to the damage-released odours of conspecifics, rapidly switching from foraging to risk-adverse behaviours [12, 17, 23]. The damage-released odour effectively acts as an honest indicator of a predation event in the local environment, and through associative coupling of these cues with predator cues (e.g., visual, chemical) prey learn to identify threats [24].…”
Section: Introductionmentioning
confidence: 99%